Textile UWB Antenna with Metamaterial for Healthcare Monitoring. (13th December 2021) - Parameswari, S.; Chitra, C.
Abstract : A new metamaterial-based UWB band-notched textile antenna for body area network (BAN) with an operational frequency range of 3 GHz to 11 GHz is created in this paper. The ultra-ide band (UWB) frequency band is covered by the antenna (3.1 GHz to 10.6 GHz). The antennas are smaller because of the usage of denim (jeans) material, which has a permittivity of 1.67. To increase the impedance transmission capacity, the ground plane is reduced to a partly rectangular conductive substance. The hexagonal cut on the bottom side is utilised to boost bandwidth by enhancing the electric field dispersion at the edges. The fabrication is built of a 1 mm thick denim (jeans) substrate, and the feed is a traditional microstrip feed. The return loss and gain characteristics of the proposed antenna are investigated. The performance of a specified antenna is investigated step by step with variable feed length, feed breadth, and substrate properties.